Review on dietary supplements as an effective improvement of Alzheimer’s disease: focus on structures and mechanisms - Sheng Li; Yinling Wei; Zhenzhen Liang; Lingli Guo; Xiaojiang Hao; Yu Zhang (Food Science and Human Wellness)
Alzheimer’s disease (AD), the major form of neurodegenerative diseases that can severely impede normal cognitive function, makes it one of the most common fatal diseases. There are currently over 50 million AD patients worldwide. The neuropathology of AD is perplexing and there is a scarcity of disease-modifying treatments. Currently, early diagnosis of AD has been made possible with the discovery of biological markers associated with pathology, providing strong support for the improvement of the disease status. The search for inhibitors of AD markers from dietary supplements (DSs) has become a major hot topic. Especially with the widespread use of DSs, DSs containing polyphenols, alkaloids, terpenes, polysaccharides and other bioactive components can prevent AD by reducing Aβ deposition, inhibiting tau protein hyperphosphorylation, reconstructing synaptic dysfunction, weakening cholinesterase activity, regulating mitochondrial oxidative stress, neuronal inflammation and apoptosis. This review summarizes the anti-AD effects of the main DSs and their bioactive constituents, as well as the potential molecular mechanisms covers from 2017 to 2023. Additionally, we discussed the opportunities and challenges faced by DSs in the process of AD prevention and treatment, aiming to further provide new perspectives for functional food development.